2018
DOI: 10.18502/kss.v3i8.2517
|View full text |Cite
|
Sign up to set email alerts
|

The Development of CSR Implementation in Indonesia and Its Impact on Company’s Financial and Non-financial Performance

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The implementation of CSR in Romania concluded that there is a positive relationship between CSR and the value of the company reaching above 75% [28]. Meanwhile, in Indonesia, CSR implementation is still low, below 50% on average [29]. FFB theft in state-owned plantations is very massive and serious.…”
Section: Optimization Of Corporate Social Responsibility Funds For Plantation Soes To Prevent Palm Oil Theftmentioning
confidence: 99%
“…The implementation of CSR in Romania concluded that there is a positive relationship between CSR and the value of the company reaching above 75% [28]. Meanwhile, in Indonesia, CSR implementation is still low, below 50% on average [29]. FFB theft in state-owned plantations is very massive and serious.…”
Section: Optimization Of Corporate Social Responsibility Funds For Plantation Soes To Prevent Palm Oil Theftmentioning
confidence: 99%
“…The Indonesian Government has released Law Number 40 2007 on Limited Liability Companies (UU Number 40 Tahun 2007 tentang Perseroan Terbatas). This law has j SOCIAL RESPONSIBILITY JOURNAL j made Indonesia the first nation in the world to mandate companies to conduct CSR and report their CSR activities (Maris, 2014;Ridho, 2018;Rosser and Edwin, 2010;Waagstein, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As the world's fourth most populous nation with more than 267 million population, Indonesia has the largest economy in Southeast Asia (Worldbank, 2020). As one of the biggest developing country, Indonesia has been trying to implement CSR for almost two decades (Ridho, 2018). The Public Interest and Research Advocacy (PIRAC) survey in 2001 showed that CSR funds in Indonesia were $11.5m from 180 organizations endorsing 279 CSR activities (PIRAC, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…40 2007 on Limited Liability Companies. Under this law, companies with activities related to natural resources are obliged to practice CSR and disclose their CSR activities (Ridho, 2018; Waagstein, 2011).…”
Section: Introductionmentioning
confidence: 99%